Resettlement processes in Colombia: Is this a measure of both adaptation and the protection of the human rights of communities affected by climate change? [Procesos de reasentamiento en Colombia: ¿una medida de adaptación y protección de derechos humanos de las víctimas del cambio climático?] (2018)
This article presents the deficiencies of the legal system in relation to resettlement of communities as an exceptional measure of climate change adaptation and protection of human rights. Among the deficiencies under analysis: the lack of an adequate conceptualization of resettlement, lack of public policy regarding resettlement and its relation to climate change adaptation, and the granting of broad discretional powers to municipal governments to undertake resettlement process that, in practice, are implemented through informal actions - with out specific regulation and protocols that guide its implementation - that have caused violations of human rights. This document is the result of an investigation that supported the construction of a report to the Inter-American Commission of Human Rights, through both exploratory and analytical documentary research and the study of and intervention in real cases. © 2018 Pontificia Universidad Javeriana. All rights reserved.